Atypical measures of diffusion at the gray‐white matter boundary in autism spectrum disorder in adulthood. Issue 2 (23rd October 2020) - Bletsch, Anke; Schäfer, Tim; Mann, Caroline; Andrews, Derek S.; Daly, Eileen; Gudbrandsen, Maria; Ruigrok, Amber N. V.; Dallyn, Robert; Romero‐Garcia, Rafael; Lai, Meng‐Chuan; Lombardo, Michael V.; Craig, Michael C.; et al.
Abstract: Autism spectrum disorder (ASD) is a highly complex neurodevelopmental condition that is accompanied by neuroanatomical differences on the macroscopic and microscopic level. Findings from histological, genetic, and more recently in vivo neuroimaging studies converge in suggesting that neuroanatomical abnormalities, specifically around the gray‐white matter (GWM) boundary, represent a crucial feature of ASD. However, no research has yet characterized the GWM boundary in ASD based on measures of diffusion. Here, we registered diffusion tensor imaging data to the structural T1‐weighted images of 92 adults with ASD and 92 matched neurotypical controls in order to examine between‐group differences and group‐by‐sex interactions in fractional anisotropy and mean diffusivity sampled at the GWM boundary, and at different sampling depths within the superficial white and into the gray matter. As hypothesized, we observed atypical diffusion at and around the GWM boundary in ASD, with between‐group differences and group‐by‐sex interactions depending on tissue class and sampling depth. Furthermore, we identified that altered diffusion at the GWM boundary partially (i.e., ~50%) overlapped with atypical gray‐white matter tissue contrast in ASD. Our study thus replicates and extends previous work highlighting the GWM boundary as a crucial target of neuropathology in ASD, and guides future work elucidating etiological mechanisms. Abstract : The present study observed atypical diffusion at and around the gray‐white matter (GWM) boundary in individuals with autism spectrum disorder (ASD) relative to neurotypical controls, with between‐group differences and group‐by‐sex interactions depending on tissue class and sampling depth. Altered diffusion at the GWM boundary was further identified to partially (i.e., ~50%) and nonrandomly overlap with atypical gray‐white matter tissue contrast in ASD. The study thus replicates and extends previous work highlighting the GWM boundary as a crucial target of neuropathology in ASD, and guides future work elucidating etiological mechanisms.